RETRACTED: Hydrophysical factors affecting the distribution of chlorophyll "a" in a small lake - Zdorovennova Galina; Zdorovennov Roman; Palshin Nikolay; Bogdanov Sergey; Smirnov Sergey; Nikulina Anna; Efremova Tatiana (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001